Sparganosis (Spirometra) in Europe in the Molecular Era - Kuchta, Roman; Kołodziej-Sobocińska, Marta; Brabec, Jan; Młocicki, Daniel; Sałamatin, Rusłan; Scholz, Tomáš (Clinical infectious diseases, 2021)
Sparganosis is a relatively neglected foodborne and waterborne disease caused by species of the tapeworm genus Spirometra, the global distribution of which has not been sufficiently recognized. Known mainly as a zoonosis of East Asia, its species are native to all inhabited continents including Europe. Spirometra has been reported from numerous wildlife species from 17 European countries, and a critical review confirmed 17 autochthonous and 8 imported human clinical cases. We present the first molecular evidence of the coincident presence of 2 species in Europe and review the current distribution to raise awareness of the parasite in this region. Spirometra erinaceieuropaei is restricted to Europe and Spirometra mansoni represents a lineage distributed mainly across Asia and Oceania that reaches Europe. The parasite is common in Eastern Europe and its distribution has potential to expand along with its invasive or migrating mammal hosts, spreading the risks of human infection.
Keywords: Zoonoses; Asia; Spirometra; zoonosis; Sparganosis; Animals; Asie; sparganóza; Humans; lidé; zoonózy; epidemiology; zvířata; emerging infectious disease; Evropa; Europe; Cestoda